Pengaruh Gulma terhadap Komponen Pertumbuhan Beberapa Kultivar Kedelai (Glycine max (L.) Merr.) - Doni Hariandi; Didik Indradewa; Proto Yudono (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2017)
The Research aims to identify the effects of weed on the growth parameters of soybean cultivars. This field research is arranged using split plot withthree blocks as the repetition where the main plot is the weed treatments and those are weed-free, weeding in a critical period, and weedy. Sub-plot is the soybean cultivars which are Anjarmoro, Argomulyo, Burangrang, Gema, Gepak kuning, Kaba, and Wilis. Theresearch’s result shows the weed treatments would affect no significant difference in the plant height, diameter of steam, and light interception, which affects are the characteristics of each soybean cultivars.